Echinococcus infections in the Baltic region - Marcinkute, Audrone; Sarkunas, Mindaugas; Moks, Epp; Saarma, Urmas; Jokelainen, Pikka; Bagrade, Guna; Laivacuma, Sniedze; Strupas, Kestutis; Sokolovas, Vitalijus; Deplazes, Peter (Veterinary Parasitology, 2017)
In the Baltic countries, the two zoonotic diseases, alveolar echinococcosis (AE) caused by Echinococcus multilocularis, and cystic echinococcosis (CE) caused by Echinococcus granulosus, are of increasing public health concern. Observations from Estonia, Latvia and Lithuania indicate that the distribution of both parasites is wider in the Baltics than previously expected. In this paper, we review and discuss the available data, regarding both parasitoses in animals and humans, from the Baltic countries and selected adjacent regions. The data are not easily comparable but reveal a worrisome situation as the number of human AE and CE cases is increasing. Despite improvements in diagnostics and treatment, AE has a high morbidity and mortality in the Baltic region. For the control of both zoonoses, monitoring transmission patterns and timely diagnosis in humans as well as the development of local control programs present major challenges. (C) 2015 Published by Elsevier B.V. Peer reviewed